2022
DOI: 10.1111/jace.18434
|View full text |Cite
|
Sign up to set email alerts
|

Improved adhesion of TiN coatings on Al2O3–carbide composites by DFT calculations and experimental arc‐PVD synthesis

Abstract: Electronic and atomic structures of interfaces between TiN coatings and Al2O3–WC composites were investigated by Density functional theory (DFT) calculations. As typical examples, interfacial orientation relationships of TiN(001)/Al2O3(0001), TiN(001)/WC(0001), TiN(111)/Al2O3(0001), and TiN(111)/WC(0001) were chosen. It was found that the TiN(111)/Al2O3(0001) and TiN(111)/WC(0001) interfaces have interfacial structural units of six‐fold coordinated triangular prisms centered on Ti atoms. In contrast, those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It was reported that proper control of crystal orientation of the TiN coatings on the CMC substrates can successfully increase overall mechanical strengths of the whole CMC systems. 205)…”
Section: Interfacial Strengthening In Al 2 O 3 -Wc Composites By Addi...mentioning
confidence: 99%
“…It was reported that proper control of crystal orientation of the TiN coatings on the CMC substrates can successfully increase overall mechanical strengths of the whole CMC systems. 205)…”
Section: Interfacial Strengthening In Al 2 O 3 -Wc Composites By Addi...mentioning
confidence: 99%